Peckia veropeso sp. nov., a flesh fly (Diptera: Sarcophagidae) from the Brazilian Amazon associated with riparian habitats - Carvalho-Filho, Fernando Da Silva; Soares, Jessica Maria Menezes; Souza, Caroline Costa De; Gorayeb, Inocêncio De Sousa (Zootaxa, 2016)
A new species of Sarcophagidae, Peckia (Peckia) veropeso sp. nov., is described based on adult male specimens collected on organic residues in an urban open air market located on the riverside in Belém, Pará state, Brazil, and in a nearby inundated forest. This species seems to be restricted to periodically inundated riparian habitats locally known as “várzea”. The distiphallus of this species is similar to that of members of the monophyletic hilifera (Aldrich)-group in the subgenus Peckia Robineau-Desvoidy. It is distinguished from the other species in the subgenus by characteristics of the male terminalia, mainly in the shape of cercus and vesica. A modified key to species of the subgenus Peckia is included.